In what ways have the staffing trends of expatriates changed and how valuable are they to MNCs? - Tonks, Danielle (2012)
This thesis aims to understand the issues of expatriation as well as the potential beneficial factors of their employment. Therefore, understanding the value of expatriates to global players is the key basis to this research.